PENGARUH PRODUK DAN HARGA TERHADAP LOYALITAS KONSUMEN MELALUI KEPUTUSAN PEMBELIAN KOPI DI KABUPATEN JOMBANG : Studi Kasus: Cafe Sunny - Siti Nafisatul Azizatul Qumairoh; Siti Nur Qomariyah (Bussman Journal : Indonesian Journal of Business and Management, 2023)
This research was conducted with the aim to determine the effects of product and price on consumer loyalty through coffee purchasing decisions carried out at the Sunny Jombang café. Product and prices have an important role in the process of creating consumer loyalty because products are things that are traded, while prices are things that act as a medium of exchange to get the desired product. In order to create consumer loyalty, consumer must go through the purchasing decision proses for product, in this study the metho iused was quantitative research method with a total sample taken of 96 respondent and questionnaires distributed using the probability sampling method of simple random sampling. From the research that has been done, the results are as follows: 1) product have has an effect on purchasing decisions 2) prices have effect on purchasing decisionsi 3) product have no effect on consumer loyalty 4) prices have an effect on consumer loyalty 5) purchase decisions have had an effect on consumer loyalty 6) product influence consumer loyalty through the purchasing decision of Sunny Jombang café consumer 7) prices affect consumer loyalty through the purchasing decision of the Sunny Jombang café consumer